2018
DOI: 10.1016/j.jsbmb.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin B links vitamin D deficiency and pediatric obesity: Direct negative regulation by vitamin D

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In humans, plasma fetuin B levels are increased in obese individuals with hepatic steatosis (36) and T2D, and associated positively with intrahepatic triglyceride and insulin resistance (36, 58). However, the mechanism underlying its role in these pathogeneses remains unclear.…”
Section: Fetuin Bmentioning
confidence: 99%
“…In humans, plasma fetuin B levels are increased in obese individuals with hepatic steatosis (36) and T2D, and associated positively with intrahepatic triglyceride and insulin resistance (36, 58). However, the mechanism underlying its role in these pathogeneses remains unclear.…”
Section: Fetuin Bmentioning
confidence: 99%
“…Recently, several epidemiological and experimental studies have indicated that VD supplementation is effective in reducing body weight, body-mass index, and fat mass and is associated with decreased levels of low-density lipoprotein cholesterol (32,33). In this study, we investigated whether the effects of maternal VD status during pregnancy and lactation had a long lasting adverse effect on the progress of obesity in the male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2DGE-based study, vitamin D deficient children are reported to have diminished serum abundances of adiponectin (ADIPOQ) [189]. In a separate 2DGE-based study, the same group reports fetuin-b (FETUB) to be elevated in the plasma of obese vitamin D deficient children compared with their vitamin D sufficient counterparts [190]. However the authors do not directly identify FETUB and rely on comparison of their findings to those of another study [191].…”
Section: Vitamin Dmentioning
confidence: 99%